1970
DOI: 10.3329/taj.v20i2.3072
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Pneumonia in Children– A Community Survey

Abstract: Pneumonia was the leading common cause of death in young children in Bangladesh. 351 patients of Pneumonia below five years of age were selected as per WHO guidelines. Out of 351 patients, one patient died due to very severe pneumonia that had history of low birth weight and malnutrition. The following factors were taken into consideration such as age, sex, low birth weight, feeding pattern, malnutrition, housing, paternal education, ventilation of living room and smoking habits of parents. It was found that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Most of our findings are consistent with risk factor analyses in previous pneumonia studies [17, 18]. Similarly, risk factors associated with mortality, such as low weight for age, lack of access to safe drinking water, and presence of at least one co-morbid condition, were also consistent with previous studies [19, 20].…”
Section: Discussionsupporting
confidence: 92%
“…Most of our findings are consistent with risk factor analyses in previous pneumonia studies [17, 18]. Similarly, risk factors associated with mortality, such as low weight for age, lack of access to safe drinking water, and presence of at least one co-morbid condition, were also consistent with previous studies [19, 20].…”
Section: Discussionsupporting
confidence: 92%
“…2 Previous research has shown that in low resource settings, risk factors for pneumonia in children have included malnutrition, inadequate paternal education, bad ventilated living room, and smoking habits of parents. 3 Pneumonia is an important cause of morbidity and mortality of children especially in developing countries. The Nepal Department of Health Services reported that acute respiratory illness (ARI) is the number one killer disease of children in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…Childhood pneumococcal vaccination had indirect effects on the incidence of pneumococcal disease [46]. Risk factors for mortality in children with pneumonia included convulsions, age <12 months, lower weight, unsafe water consumption, lower parental education, severity of disease, and presence of co-morbid conditions [47,48,49,50,51].…”
Section: Discussionmentioning
confidence: 99%